Discrete element simulation study on fracture propagation law of dual well synchronous fracturing - ZHANG Jiawei, LIU Xiangjun, XIONG Jian, LIANG Lixi, REN Jianfei, LIU Baiqu (Youqicang pingjia yu kaifa)
The understanding of fracture propagation and evolution during dual well synchronous hydraulic fracturing, particularly under various conditions, remains limited. Meanwhile, the interaction between fractures will cause fracture reorientation and affect the hydraulic fracturing effect. In order to solve these problems, the fracture propagation law and failure mode under the influence of different factors are studied by the discrete element method. The results show that when the angle between the interwell connecting line and the maximum principal stress （θ） is 0°, and under the influence of the horizontal stress difference, the stress around the borehole wall can be divided into two stages: the stable stage before the fracture intersection and the steep rise stage after the fracture intersection. With the decrease of the horizontal principal stress difference, the failure mode changes from single fracture to multi fracture failure. When θ≠0°, the in-situ stress field of the formation changes, which causes the fracture deflection and forms an inclined fracture connecting the two wells. During the fracturing process, the expansion of the fracture exerts great stress on the surrounding area, and the magnitude and direction of local stress state change due to the expansion of the main fracture. So that the crack spreads away from the direction of the maximum principal stress.